DIGITAL RISK OVERSIGHT IN THE PUBLIC SECTOR : BETWEEN INNOVATION AND INSTITUTIONAL LIMITS - Matheus Gratiano Mali; Natta Sanjaya; Citra Mugi Rahayu (Natapraja, 2026)
Digital transformation has become essential for strengthening risk-based public sector oversight. In Indonesia, however, digital supervision remains fragmented and uneven, with limited integration under the Electronic-Based Government System (SPBE). This study examines how digital technologies are applied to enhance risk management and oversight in the Special Region of Yogyakarta. Using a qualitative case study approach, data were collected through in-depth interviews with key stakeholders, including BPKP, the Regional Inspectorate, BPKA, and Diskominfo. The findings show that applications such as SIWARIS, SIPETIR, SIPD, and RMIS have improved efficiency, transparency, and risk visibility; however, their effectiveness is constrained by limited interoperability, fragmented systems, low digital literacy, and weak enforcement authority. As a result, risk management remains largely reactive, with digital tools functioning more as compliance mechanisms than as preventive systems. This study highlights the paradox of partial digitalization and contributes to digital governance literature by emphasizing that effective digital oversight requires integrated systems, early warning capabilities, and a risk-aware institutional culture.